Colisional Cloud Debris and Propelled Evasive Maneuvers - Ferreira, L. S.; Jesus, A. D.C.; Carvalho, T. C.F.; Sousa, R. R. [UNESP] (IOP Publishing, 2017)
Space debris clouds exist at various altitudes in the environment outside the Earth. Fragmentation of debris and/or collision between the debris of a cloud increases the amount of debris, producing smaller debris. This event also increases significantly the chances of collision with operational vehicles in orbit. In this work we study clouds of debris that are close to a spacecraft in relation to its distance from the center of the Earth. The results show several layers of colliding debris depending on their size over time of evasive maneuvers of the vehicle. In addition, we have tested such maneuvers for propulsion systems with a linear and exponential mass variation model. The results show that the linear propulsion system is more efficient.